2009
DOI: 10.1523/jneurosci.1614-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mental Training Enhances Attentional Stability: Neural and Behavioral Evidence

Abstract: The capacity to stabilize the content of attention over time varies among individuals, and its impairment is a hallmark of several mental illnesses. Impairments in sustained attention in patients with attention disorders have been associated with increased trial-to-trial variability in reaction time and event-related potential deficits during attention tasks. At present, it is unclear whether the ability to sustain attention and its underlying brain circuitry are transformable through training. Here, we show, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
343
3
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(382 citation statements)
references
References 40 publications
(83 reference statements)
30
343
3
6
Order By: Relevance
“…A prediction from a cognitive training perspective is that repeatedly engaging in core cognitive control processes involving attentional orienting and selection, sustained attention, WM maintenance, and control over mind wandering as part of MT practice, will lead to corresponding strengthening and enhancement of these processes (see Lutz et al 2009;Morrison et al 2014;Morrison and Jha 2015). In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 99%
“…A prediction from a cognitive training perspective is that repeatedly engaging in core cognitive control processes involving attentional orienting and selection, sustained attention, WM maintenance, and control over mind wandering as part of MT practice, will lead to corresponding strengthening and enhancement of these processes (see Lutz et al 2009;Morrison et al 2014;Morrison and Jha 2015). In line with this prediction, several prior studies have demonstrated that MT can improve performance on measures of selective and sustained attention (e.g., Allen et al 2012;Jensen et al 2012;Jha et al 2007;MacLean et al 2010;Zanesco et al 2013), and WM (Chambers et al 2008;Jensen et al 2012;Mrazek et al 2013;Quach et al 2016;Van Vugt and Jha 2011;Zeidan et al 2010; but see Morrison et al 2014), and can reduce performance lapses associated with mind wandering Morrison et al 2014;Mrazek et al 2013).…”
mentioning
confidence: 99%
“…Most meditation practices are aimed to better manipulate the mind, brain function and physical state through mindfulness concentration and respiratory regulation. Having been adopted as the complementary medical practices, meditation inspired more scientific studies on its physiological and mental effects [10] [11] [12]. Meditation researches are mostly focused on Yoga and transcendental meditation from India, Japanese Zen, and Tibetan Buddhism [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Meditation might be a possible candidate in the quest for such a positive approach as there is ample evidence for its beneficial effects for a number of cognitive domains, including attention, memory, verbal fluency, executive function, processing speed, overall cognitive flexibility as well as conflict monitoring and even creativity (Lutz et al, 2008(Lutz et al, , 2009Colzato et al, 2012;Gard et al, 2014;Lippelt et al, 2014;Marciniak et al, 2014;Newberg et al, 2014). This wealth of cognitive studies did not only further support the idea that the human brain (and mind) is plastic throughout life but also lead to a number of relevant concepts and theories, such as that meditation is associated with an increasing control over the distribution of limited brain resources (Slagter et al, 2007) as well as with process-specific learning, rather than purely stimulus-or task-specific learning (Slagter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%